ANALISIS TENTANG FAKTOR MASYARAKAT MEMILIH DAN TIDAK MEMILIH SISWAJA MULJADI SEBAGAI ANGGOTA LEGISLATIF DPRD PROVINSI RIAU TAHUN 2014 DAPIL IV ROKAN HILIR - Erlinda, Sri; ', Suyeni; ', Zahirman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: this research was conducted to view and understand of predominance of minority candidate in legislative election. Problem of this research is Society’s factors in election of electors and non-electors of choosing Siswaja Mulyadi as a legislative member of “DPRD Riau 2014 region IV Rokan Hilir”. this research aims to find out Society’s reason factors as elector of Siswaja Mulyadi and non-electors of Siswaja Mulyadi in legislative election. Population of this research was all society of Rohillisted in legislative election of DPRD Riau 2014 in total 406.022. Sample was taken by Sugiyono’s technique by 50 electors and 50 non-electors. Research used a qualitative descriptive method. Result shows that the main reason of society in choosing Siswaja Mulyadi as a legislative member of “DPRD Riau 2014”,41 respondents (82%) caused by self-adaptation factor by Siswaja Mulyadi showed that his ability in socialization to society was good. The main reason of society in not choosing SiswajaMulyadi as a legislative member of “DPRD Riau 2014”, 40 respondents (80%) caused by his religion. These results show that there is some of people are tending to select candidate based on certain religion, or certain religionbased political party .Keywords: Factors in Election of Electors And Non-Electors of chosing, Legislative